Etika Politik Islam dalam Konsep Kenegaraan Moh. Natsir dan S.M. Kartosuwiryo: Analisis Filsafati-Komparatif - Munandar, Aris; Suwendi, Suwendi; Susanti, Endang (Pascasarjana UIN ANTASARI Banjarmasin, 2025)
This study examines Islamic political ethics in the thought of Mohammad Natsir and Sekarmadji Maridjan Kartosuwiryo through a philosophical-comparative approach. The two figures represent opposing poles in the discourse on Islam and the state in Indonesia, Natsir with his inclusive constitutional-democratic approach, and Kartosuwiryo with his exclusive theocratic-revolutionary vision. The study focuses on the construction of political ethics in their views on democracy, power, law, and plurality within the context of the modern state. This research employs a qualitative method based on library research, with thematic analysis of primary and secondary works by both figures. A philosophical approach is used to explore the moral-political dimensions of ethics, including the normative basis of political action, the legitimacy of authority, and the relationship between religion and the state. The findings reveal fundamental differences: Natsir perceives democracy as an ethical and constitutional means to promote Islamic values peacefully, while Kartosuwiryo considers only a theocratic system based on sharia as legitimate, rejecting democratic states entirely. These differences are also reflected in their concepts of power, law, and plurality Natsir emphasizes inclusivity and public ethics, while Kartosuwiryo adopts an exclusive and confrontational stance. This study not only clarifies the divergent paradigms of postcolonial Islamic political ethics in Indonesia but also offers theoretical contributions to understanding the relevance of constitutional versus revolutionary approaches in contemporary Islamic politics.